Alternatipathes Molodtsova & Opresko 2017 - Lima, Manuela M.; Cordeiro, Ralf T. S.; Perez, Carlos D. (Zenodo, 2019)
Genus Alternatipathes Molodtsova & Opresko, 2017 Type-species. Umbellapathes bipinnata Opresko, 2005 (by original designation). Diagnosis. Corallum attached to substrate; monopodial, unbranched or branched, and pinnulate. When present, pinnate branches of the first, second, and rarely third order arise from lowermost pinnules of stem. Pinnules simple, arranged alternately (including lowermost pair) in two lateral rows. Length of pinnules decreasing regularly from lower pinnulated section of stem to apex, forming a somewhat triangular outline. Striatum absent. Spines conical, smooth, simple (or rarely forked), with acute to slightly rounded apex and flared base. Spines larger on polypar side of pinnule. Size of spines apparently increases in older colonies. Polyps 2–4 mm in transverse diameter; arranged in one row with up to three polyps per centimeter. (Molodtsova & Opresko, 2017). Distribution. Pacific and Indian Ocean (Opresko, 2005; Molodtsova & Opresko, 2017), South Atlantic, South Georgia Island (Smithsonian, USNM 99488, identified by D. M. Opresko; available in <http://collections.nmnh. si.edu/search/iz/>) and Antarctica (Smithsonian, USNM 78800, 78802, 78804, 78806, 78811, identified by D. M. Opresko; available in <http://collections.nmnh.si.edu/search/iz/>). Published as part of Lima, Manuela M., Cordeiro, Ralf T. S. & Perez, Carlos D., 2019, Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic, pp. 1-67 in Zootaxa 4692 (1) on pages 46-47, DOI:10.11646/zootaxa.4692.1.1, http://zenodo.org/record/3528942